Reducing semiconductor optical Amplifier’s non-linearity through probabilistic amplitude shaping of optical QAM signal - Ahmed, Shujja; Ghafoor, Salman; Aziz, Bilal; Aljohani, Abdulah Jeza; Imran, Muhammad; Ijaz, Muhammad; Poti, Luca (Frontiers in Physics, 2026)
Optical communication is an efficient technology for high-speed, long-distance data transmission. Semiconductor optical amplifiers (SOAs) are particularly promising for optical signal amplification in O-band transmission due to their compact size, low power consumption, and ease of integration into photonic networks. However, SOA-based systems suffer from nonlinear impairments, which degrade signal quality, especially at higher amplification levels. These nonlinear effects arise from changes in the intrinsic properties of the SOA’s waveguide material, such as refractive index variations, when subjected to high optical field intensities. In this paper, we investigate the potential of probabilistic amplitude shaping (PAS) as a signal-shaping technique to mitigate SOA-induced nonlinearities. PAS leverages a non-uniform probability distribution of constellation points (e.g., QAM symbols) to reduce the average transmit power while maintaining the same information rate. Our simulation results demonstrate that applying PAS to standard QAM signals significantly improves received signal quality, as measured by bit error rate (BER), error vector magnitude (EVM), and mutual information (MI), compared to conventional uniform QAM signaling. Furthermore, forward error correction (FEC) is employed to further enhance the system performance.